2018
DOI: 10.1103/physrevd.97.091503
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamization in kinetic theory: Transient modes and the gradient expansion

Abstract: We explore the transition to hydrodynamics in a weakly-coupled model of quark-gluon plasma given by kinetic theory in the relaxation time approximation with conformal symmetry. We demonstrate that the gradient expansion in this model has a vanishing radius of convergence due to the presence of a transient (nonhydrodynamic) mode, in a way similar to results obtained earlier in strongly-coupled gauge theories. This suggests that the mechanism by which hydrodynamic behaviour emerges is the same, which we further … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
167
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(184 citation statements)
references
References 67 publications
16
167
1
Order By: Relevance
“…The analysis of these large order perturbations showed that the hydrodynamic expansion is an asymptotic series, exhibiting a factorial growth of the series coefficients. Similar behaviour was found in different ultraviolet completions of second order hydrodynamics [26][27][28] and kinetic theory in the relaxation time approximation (RTA) [29] (see also [30] for a complementary analysis of the convergence of the hydrodynamic series). Interestingly, the analysis of these series via Borel-Padé techniques showed that these large order gradient expansions are sensitive to non-hydrodynamic modes, which play an equivalent role to non-perturbative corrections in perturbation theory.…”
Section: Jhep04(2018)042supporting
confidence: 68%
See 1 more Smart Citation
“…The analysis of these large order perturbations showed that the hydrodynamic expansion is an asymptotic series, exhibiting a factorial growth of the series coefficients. Similar behaviour was found in different ultraviolet completions of second order hydrodynamics [26][27][28] and kinetic theory in the relaxation time approximation (RTA) [29] (see also [30] for a complementary analysis of the convergence of the hydrodynamic series). Interestingly, the analysis of these series via Borel-Padé techniques showed that these large order gradient expansions are sensitive to non-hydrodynamic modes, which play an equivalent role to non-perturbative corrections in perturbation theory.…”
Section: Jhep04(2018)042supporting
confidence: 68%
“…By varying the amplitude of those non-perturbative corrections we observe that the convergence of different initial configurations towards the attractor occurs at values of the viscosity-rescaled gradient for which the resummation has hydrodynamized. We also perform an identical analysis of the hydrodynamic series of RTA kinetic theory [29] and find that in this model both hydrodynamization and convergence to the attractor solution occurs at smaller viscosity-rescaled gradients than in the strong coupling computations. This paper is organised as follows: in section 2 we review the main properties of boost invariant flow and holographic Gauss-Bonnet to set up the notation, define the main quantities and outline the strategy to compute large order gradient corrections in this highercurvature theory.…”
Section: Jhep04(2018)042mentioning
confidence: 99%
“…In Minkowski space with 1 Previous studies of the Bjorken model have shown that after rewriting the hydrodynamical equations for the temperature and the only independent component of the shear viscous tensor in terms of the variable w ¼ τTðτÞ (where τ and T are the longitudinal proper time and temperature) reduce effectively to a truly 1D nonlinear differential equation [20,26,27,36,37]. The solution of this equation for a suitable initial condition determines what has been, by abuse of terminology, called the "attractor solution."…”
Section: Setupmentioning
confidence: 99%
“…Previous works have focused on fluids undergoing Bjorken flow [20,26,27,36,37] and nonhomogeneous expanding plasmas [39]. We expand these studies by investigating the properties of the attractors in the plasmas undergoing Gubser flow [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that a size of 0.5 fm was feasible, which was later refined to 1/T by an explicit computation using 5-dimensional numerical general relativity [35]. The second and third constraint are studied in [36][37][38][39], where it was concluded that hydrodynamics breaks down for momentum modes of |k| > 4.5T , which translates into a size λ 2π/|k| > 1.4/T . 2 So perhaps unsurprisingly all three constraints give a similar outcome.…”
Section: Small Systemsmentioning
confidence: 99%